PENINGKATAN PRODUKTIVITAS DAN PROFITABILITAS BAGI UKM SENTRA INDUSTRI KUE BAKPIA DI GEMPOL PASURUAN JAWA TIMUR - Ulfi Pristiana; Cholis Hidayati; Bambang Wiwoho (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2015)
This service community program was being carried out in the center of Bakpia industry at Gempol district in Pasuruan city namely SME bakpia cake â€œBarokah Jayaâ€ and SME bakpia cake â€œBerlianâ€. Lately, this business has been running well but is not optimal. One of the identified problem is that the production process was done manually and consuming time so that the processing becomes less efficient. The condition is leading the partners can not meet consumer demand. The purpose of this program is to assist these home industries in an effort to increase productivity with the aid of a stirrer machine which is expected to improve the productivity and profitability of the business. The assisting method was performed by conditioning the object. There were 2 kinds of program implementation, management training and giving a stirrer machine for materials processing. Training is done in the field of management, that is finance, marketing and entrepreneurship as well as manufacturing. The stirrer machine is aimed to change the manual production process into mechanical production process. The assistance program turns out to be very helpfull in improving the efficiency of time in the processing of raw materials. They can now improve the product quantity significantly. The management training is also creating some beneficials. The product becomes more hygenics,the packaging is more interesting and the market is enhancing, the demand is increasing and even they are now keeping the business record administratively.Keyword: Productivity. Profitability